2007
DOI: 10.1016/j.ydbio.2007.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Notch signaling relieves the joint-suppressive activity of Defective proventriculus in the Drosophila leg

Abstract: Segmentation plays crucial roles during morphogenesis. Drosophila legs are divided into segments along the proximal-distal axis by flexible structures called joints. Notch signaling is necessary and sufficient to promote leg growth and joint formation, and is activated in distal cells of each segment in everting prepupal leg discs. The homeobox gene defective proventriculus (dve) is expressed in regions both proximal and distal to the intersegmental folds at 4 h after puparium formation (APF). Dve-expressing r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 60 publications
0
24
0
Order By: Relevance
“…Such regulation of the membrane availability of Notch could equally affect Dlmediated activation, although Ser appears to be the major ligand responsible in the joints (Bishop et al, 1999). Other factors are likely to influence proximal repression of N because ectopic joints are also observed in alterations of the EGFR pathway (Galindo et al, 2005) and mutants of defective proventriculus (Shirai et al, 2007). We note also that the domains of N activation (both normal and ectopic) extend beyond the cells at the interface with Ser.…”
Section: Discussionmentioning
confidence: 72%
“…Such regulation of the membrane availability of Notch could equally affect Dlmediated activation, although Ser appears to be the major ligand responsible in the joints (Bishop et al, 1999). Other factors are likely to influence proximal repression of N because ectopic joints are also observed in alterations of the EGFR pathway (Galindo et al, 2005) and mutants of defective proventriculus (Shirai et al, 2007). We note also that the domains of N activation (both normal and ectopic) extend beyond the cells at the interface with Ser.…”
Section: Discussionmentioning
confidence: 72%
“…Among GAL4 drivers inserted near the genes reported to show segmental expression in the tarsus, we found three drivers which were expressed in different but overlapping populations of cells in the joint region: big brain (bib)-GAL4, neuralized (neur)-GAL4 and fringe (fng)-GAL4 (de Celis et al, 1998;Mirth and Akam, 2002;Rauskolb and Irvine, 1999;Shirai et al, 2007). bib and neur were expressed in the deep region of the cavity, flanked by fng expression in cells projecting into the ridge (see Fig.…”
Section: Research Articlementioning
confidence: 99%
“…Inhibition of dve-A repression by the heat-shock mediated ubiquitous dve-A induction severely impairs the copper absorptive function (Nakagoshi et al, 1998). Furthermore, we have also shown that the temporally regulated dve repression is crucial for wing patterning and leg joint formation Shirai et al, 2007).…”
Section: Spatio-temporal Regulation Of Dve Isoforms Is Important For mentioning
confidence: 55%